Traumatic neck injury: An accidental impalement by a Needlefish - Aishath Azna Ali; Rajan Gurung; Firdaus Hayati; Andee Dzulkarnaen Zakaria; Irfan Mohamad; Ching Fui Fui @ Faihana Ching Abdullah (Elsevier, 2021)
Encounters between marine animals and humans can result in critical injury and fatal complications. We highlight a 20-y-old male who sustained a penetrating injury to the neck as a result of impalement by needlefish (Tylosurus sp) while snorkeling. He sustained a penetrating injury in the posterior triangle of the neck. On presentation, he was stabilized and received empirical antibiotics, analgesia, and anti-tetanus toxoid injection before being transferred to a tertiary center. On presentation to the tertiary hospital, the patient was hemodynamically stable with no clinical evidence of injury to surrounding neck structures, and this was confirmed using computed tomography. The patient underwent local wound exploration and retrieval of the needlefish beak under general anesthesia. The wound was left open to heal by secondary intention. The patient was discharged with oral antibiotics and went on to make a complete recovery.